(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2024)
Based on the results of the M ichelson ̆Morley experiment [1] and the direct measurement of the speed of light in two directions, we can conclude that the movement of the Earth in relation to the Sun and the movement of the solar system in relation to the center of the galaxy do not affect the measurement of the speed of light in the vicinity of the Earth. But on the other hand, based on results of the M ichelson ̆Morley experiment and the direct measurement of the speed of light in two directions we cannot know with certainty whether the Earth’s rotation around its axis affects the measurement of the speed of light in one direction. Thus, instead of the motion by which the Earth’s surface moves in relation to the Sun, we will observe the angular motion by which the Earth rotates on its axis relative to distant stars. Instead of measuring the speed of light in two directions, we will measure the speed of light in one